Data subject rights under the GDPR - Vrabec, Helena U., 1989- (Oxford : Oxford University Press, 2021)
To navigate the changing landscape and be able to pursue claims, this book gives practitioners and activists a comprehensive overview of data subject rights. It also provides readers with the historical context and theoretical underpinnings that shaped the introduction of data subject rights.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 16, 2021).
Keywords: Data protection -- Law and legislation -- European Union countries; European Parliament; Law; Laws of specific jurisdictions & specific areas of law